Arthroscopic treatment of iliopsoas impingement syndrome after hip arthroplasty - Di Benedetto, Paolo; Niccoli, Giuseppe; Magnanelli, Stefano; Beltrame, Alessandro; Gisonni, Renato; Cainero, Vanni; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the Work: Groin pain after hip arthroplasty (HA) ranges from 0.4% to 18.3%. Defining the cause of groin pain after HA can be difficult. Iliopsoas impingement (IPI) has been reported to be the underlying cause of groin pain in up to 4.4% of cases. The purpose of this study is to present arthroscopic surgical outcomes in the treatment of IPI after HA. Methods: Between September 2013 and March 2018, 13 patients, 11 total hip arthroplasty (THA), 1 hip endoprosthesis and 1 total hip resurfacing affected by groin pain due to unceasing iliopsoas tendinopathy for impingement after HA were treated arthroscopically. The patients underwent to physical examination, blood analysis, hip X-rays, bone scintigraphy and CT assessment. We performed the arthroscopic OUT-IN access to hip joint in all patients. VAS scale, Harris Hip Score (HHS) and Medical Research Council (MRC) scale were performed before surgery and during follow up at 1-3-6-12 months. Results: After 10 months of mean follow-up, average HHS and MRC scale improved significantly from preoperatively to postoperatively. No complications arose in our case series. Conclusions: Hip arthroscopy after hip arthroplasty is supported in the literature for a variety of indications. Hip arthroscopy is a viable and reproducible technique in treatment of IPI, being less invasive than the classic open technique. This simple arthroscopic release provides satisfactory results and preserves HA function. Moreover an arthroscopic OUT-IN access proves good clinical outcomes, few complications and iatrogenic lesions.